2012
DOI: 10.3899/jrheum.120106
|View full text |Cite
|
Sign up to set email alerts
|

Initial Diagnosis of Lumbar Disc Herniation Is Associated with a Delay in Diagnosis of Ankylosing Spondylitis

Abstract: These results indicate the need to increase awareness of the concept of axial spondyloarthritis among specialists who might be the first physicians consulted by patients with AS for their back pain. There is also a need to develop strategies for early referral of such patients to rheumatologists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
42
1
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(54 citation statements)
references
References 19 publications
(7 reference statements)
8
42
1
3
Order By: Relevance
“…Furthermore, the results of this study revealed that lower educational level causes longer delay in diagnosis. Similar to our results, Dincer et al 5 and Gerdan et al 7 showed a higher average of diagnostic delay in patients with low educational level compared to high educational level patients. On the other hand, in another survey by Ibn Yacoub et al, 8 educational level had no effect on diagnostic delay.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Furthermore, the results of this study revealed that lower educational level causes longer delay in diagnosis. Similar to our results, Dincer et al 5 and Gerdan et al 7 showed a higher average of diagnostic delay in patients with low educational level compared to high educational level patients. On the other hand, in another survey by Ibn Yacoub et al, 8 educational level had no effect on diagnostic delay.…”
Section: Discussionsupporting
confidence: 82%
“…Delayed Diagnosis in AS Human leukocyte antigen B27 (HLA-B27) status, educational level, sex, peripheral arthritis, extra-articular manifestations, and family history are some factors reported to affect diagnostic delay in AS; however, their results are inconsistent. [4][5][6][7][8] Improved knowledge about diagnostic delay status and associated factors in different regions of the world may help clinicians diagnose AS in earlier stages. Earlier diagnosis and efficient treatments with anti-tumor necrosis factor agents may prevent disabilities and improve the outcomes as well as decrease the government healthcare and non-healthcare costs.…”
mentioning
confidence: 99%
“…Delay in diagnosis of SpA has been described in women 5,9,10 and in both sexes 6,7,[11][12][13][14][15][16]20,26,27,29,30,32,33,35,38,39,40,44,45,46 , and although Bandinelli 23 observed less diagnostic delay in women than in men, in most of the papers where delay was compared between men and women, it was greater in women 8,17,18,19,21,22,28,31,34,37,41,42,43,47,48 . This implies that patients have had medically unsolved disorders for a long time, have continued searching for a diagnosis and treatment, or are being erroneously diagnosed and managed 49 .…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 shows the main characteristics of the 42 studies on diagnostic delay in SpA included in this systematic review 1,2,3,[8][9][10][11][12][13][14][15][16][17][18]19,20,21,22,23,[26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47]48 . The review included 23,883 patients (67.6% men, 32.3% women).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation